Language change and linguistic etiquette portrayed in the characters of the novel and movie â€œMemoirs of a Geishaâ€ - Ulinuha, Atik; Parnawati, Tantry Ajeng (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2019)
Despite the popularity of Memoirs of a Geisha around the world, both the novel and movie go along with controversy. Thus, Japanese culture presented in Memoirs of a Geisha naturally faced some adjustment especially in the way the characters communicate. This study aims to describe the intercultural communication portrayed by the characters of Memoirs of a Geisha. To deal with, a descriptive qualitative method using sociolinguistic approach was employed. The objects were a movie with a duration of 145 minutes and the novel with 448 pages. The intercultural communication portrayed by the characters was categorized into language change and linguistic etiquette. There were 45 language change and 31 linguistic etiquettes portrayed. The language changes found were in the form of both external and internal changes. Meanwhile, the linguistic etiquettes found were in the form of honorifics such as address terms, professional address terms, inferiority, and in-group honorific.Â DOI: 10.26905/enjourme.v2i2.3111Â